Co-Production in Maritime Disaster Risk Management Based on Coastal Community Participation in Pesisir Selatan Regency - Angga Putra Tri Rezeki; Aldri Frinaldi (Universitas Muhammadiyah Gorontalo, 2026)
Maritime disaster risk management in coastal areas continues to face challenges related to the limited involvement of local communities in disaster governance systems, particularly in relation to tidal flood risks. This study aims to analyse co-production practices in tidal flood risk management based on coastal community participation in Pesisir Selatan Regency, with an empirical focus on Nagari Kapuh. This study employed a descriptive qualitative approach using a grounded theory analysis strategy. Data were collected through in-depth interviews, field observations, and documentation involving 17 informants, consisting of representatives from the Regional Disaster Management Agency, subdistrict government, nagari government, kampung heads, and coastal communities affected by tidal flooding. Data analysis was conducted through the stages of open coding, axial coding, and selective coding. The findings show that co-production practices have emerged through community-based local knowledge in identifying signs of tidal flooding, tiered reporting to kampung heads and the nagari government, mutual cooperation in local response efforts, and the articulation of coastal protection needs. However, these practices remain suboptimal because coordination is still reactive, local preparedness institutions have not functioned continuously, and follow-up actions on proposed breakwater development have not been fully realised. This study formulates the Theory of Adaptive Co-Production of Coastal Communities in Tidal Flood Risk Management as a substantive theory. In conclusion, strengthening co-production should be directed towards institutionalising community participation, activating local preparedness institutions, improving risk data, and integrating community aspirations into coastal protection policies.